Microplastics increase susceptibility of amphibian larvae to the chytrid fungus Batrachochytrium dendrobatidis - Jaime Bosch (Nature Portfolio, 2021)
Abstract Microplastics (MPs), a new class of pollutants that pose a threat to aquatic biodiversity, are of increasing global concern. In tandem, the amphibian chytrid fungus Batrachochytrium dendrobatidis (Bd) causing the disease chytridiomycosis is emerging worldwide as a major stressor to amphibians. We here assess whether synergies exist between this infectious disease and MP pollution by mimicking natural contact of a highly susceptible species (midwife toads, Alytes obstetricans) with a Bd-infected reservoir species (fire salamanders, Salamandra salamandra) in the presence and absence of MPs. We found that MP ingestion increases the burden of infection by Bd in a dose-dependent manner. However, MPs accumulated to a greater extent in amphibians that were not exposed to Bd, likely due to Bd-damaged tadpole mouthparts interfering with MP ingestion. Our experimental approach showed compelling interactions between two emergent processes, chytridiomycosis and MP pollution, necessitating further research into potential synergies between these biotic and abiotic threats to amphibians.